Influence of chloride, sulphate, phosphate, and silicate-based potassium fertilizers and rice husk biochar on cadmium fate, complexation, leaching and uptake in maize under alkaline soil conditions - Muhammad Ashar Ayub; Muhammad Zia ur Rehman; Mujahid Ali; Muhammad Younas; Hesham F. Alharby; Ali Majrashi; Amnah M. Alamri; Amal A. M. Al-ghamdi (Biodegradation, 2026)

Revolutionizing the potential of laccase from Bacillus paralicheniformis as an eco-friendly solution to reduce polychlorinated dibenzofurans contamination through integrated computational approach - Muhammad Naveed; Ayesha Saleem; Tariq Aziz; Urooj Rasheed; Arooj Azeem; Maryum Rasheed; Manal F. Elkhadragy; Ashwag Shami; Hanan Abdulrahman Sagini; Rewaa S. Jalal; Hayam A. Alwabsi; Fakhria A. Al-Joufi (Biodegradation, 2026)

In situ biotransformation of synthetic glutamate to γ-amino butyric acid by an auxotrophic Lactococcus lactis in polysorbate-mediated thermoaerobic process - Siaknder Ali; Kinza Arif; Qaiser Farid Khan; Muhammad Usman Ahmad; Ifrah Shabbir; Iram Liaqat; Tawaf Ali Shah; Gehan M. Elossaily; Yousef A. Bin Jardan (Biodegradation, 2026)

Decoding the catalytic potential of a Cycloclasticus zancles ring-hydroxylating dioxygenase through computational analysis for enhanced PAH biodegradation - Muhammad Naveed; Ahmed Raza; Ahiba Adil; Abubakar Majeed; Sana Miraj Khan; Ayaz Ali Khan; Rania Ali El Hadi Mohamed; Nawal H. Siddig; Hayam A. Alwabsi; Hanan Abdulrahman Sagini (Biodegradation, 2026)

In silico evaluation of protocatechuate 4,5-dioxygenase for environmental detoxification of persistent organic pollutants - Muhammad Naveed; Maryum Rasheed; Maida Salah Ud Din; Minahil Zahid; Ayaz Ali Khan; Mayasar I. Al Zaban; Ashwag Shami; Hayam A. Alwabsi (Biodegradation, 2026)

Harnessing novel biosynthesized ZrO₂ biochar nanocomposites for reactive orange 16 dye adsorption: kinetic modeling and cytotoxicity insights - Mubashara Fayyaz; Mohamed A. Habib; Syed Kashif Ali; Saif Ullah; Muhammad Imran Kanjal; Tahreem Saleem; Rana Muhammad Zulqarnain; Ahmed B. M. Ibrahim (Biodegradation, 2026)

Modulation of arsenic uptake and detoxification in maize (Zea mays L.) by plant-based iron oxide nanoparticles - Tauseef Anwar; Huma Qureshi; Muhammad Imran; Hossam S. El-Beltagi; Salohiddinjon Yunusov; Shuqurillo Ziyadov; Muydinjon M. Muminov; Gamal Awad El-Shaboury; Dilbar Bazarbayeva; Ibtisam M. Alsudays; Khalid H. Alamer; Munisa Bekmukhamedova; et al. (Biodegradation, 2026)

Exploring the biocatalytic potential of Amycolatopsis japonica DyP in degrading plasticizer and phenolic-derived xenobiotic compounds - Muhammad Naveed; Ayesha Saleem; Tariq Aziz; Sadia Jabeen; Sana Miraj Khan; Maida Salah Ud Din; Nantenaina Tombozara; Mayasar I. Al-zaban; Ashwag Shami; Hayam A. Alwabsi (Biodegradation, 2026)

Bioremediation of aquaculture wastewater using the fungal biomass integrating Plackett–Burman design - Hazem T. Abd El-Hamid; Muhammad A. El-Alfy; Hanan M. Hafiz; Hoda M. El-Gharabawy (Biodegradation, 2026)
Aquaculture wastewater contains elevated levels of nutrients and organic pollutants that can accelerate eutrophication and impair aquatic ecosystems if discharged untreated. In the study, a fungal-based remediation approach was investigated for the removal of pollutants from aquaculture wastewater collected from Baltim Station ponds (31.55244° N, 31.092855° E) near Lake Burullus, Egypt. Two native fungal isolates, Aspergillus niger and Aspergillus flavus , were employed for primary mycoremediation experiments, while Ganoderma mbrekobenum was included only in the Plackett–Burman experimental design to evaluate the influence of environmental and nutritional factors on total phosphorus (TP) removal under optimized conditions. The fungal treatment significantly improved water quality, showing substantial reductions in total protein, phosphorus, nitrogen, organic matter, and chemical oxygen demand (COD) indicating a vital role of Aspergillus species in the bioremediation of nutrient-rich aquatic environments. The Plackett–Burman design (PBD) showed that fungal treatment significantly reduced pollutant concentrations with higher metabolic activity and enzymatic production as dehydrogenase and total protein from 9 to 12 days. Moreover, PBD identified KH 2 PO 4 and MgSO₄ as the most influential variables for enhancing TP removal in the presence of G. mbrekobenum , while peptone and yeast extract exhibited the greatest effect in the non-fungal control system. The regression models demonstrated strong predictive accuracy (R 2 > 0.99), confirming the validity of the optimization approach. The results highlight the effectiveness of fungal biomass as a cost-effective and eco-friendly bioremediation strategy for mitigating nutrient pollution in aquaculture effluents and protecting sensitive aquatic environments such as Lake Burullus.

Ex-situ multi-media bioleaching and functional characterization of indigenous fungal strains for chromium and zinc remediation in polluted soils - Ibrar Khan; Muhammad Bilal Akram; Aneela Rehman; Mujaddad Ur Rehman; Tawaf Ali Shah; Saad A. Alamri; Yasser S. Mostafa; Abdulrahman A. Almehizia (Biodegradation, 2025)

Decolorization potential of mixed microbial consortia for reactive and disperse textile dyestuffs - Muhammad Asgher; H. N. Bhatti; S. A. H. Shah; M. Javaid Asad; R. L. Legge (Biodegradation, 2007)